Post-pregnancy aspirin resistance appears not to be related with recurrent hypertensive disorders of pregnancy. (March 2017) - Abheiden, Carolien N.H.; Fuijkschot, Wessel W.; Arduç, Arda; van Diemen, Jeske J.K.; Harmsze, Ankie M.; de Boer, Marjon A.; Thijs, Abel; de Vries, Johanna I.P.
Abstract: Objective: The FRUIT-RCT concluded that low-molecular-weight heparin added to aspirin compared to treatment with aspirin alone is beneficial in the prevention of early-onset hypertensive disorders of pregnancy (HD) in women with inheritable thrombophilia and prior HD and/or a small-for-gestational age (SGA) infant leading to delivery before 34 weeks gestation. The aim of this study is to answer the question whether aspirin resistance is associated with recurrent HD. Study design: Women with and without recurrent HD matched for age, study arm, and chronic hypertension were invited for this follow-up study 6–16 years after they participated in the FRUIT-RCT. Aspirin resistance was tested after 10 days of aspirin intake using three complementary tests: PFA-200, VerifyNow ® and serum thromboxane B2 (TXB2 ). An independent t -test, Mann-Whitney U test, Fisher's Exact test and Chi 2 test were used for the statistical analyses. Results: Thirteen of 24 women with recurrent HD and 16 of 24 women without recurrent HD participated. The prevalence of laboratory aspirin resistance was 34.5% according to the PFA-200, 3.4% according to the VerifyNow ® and 24.1% according to TXB2 . The prevalence of aspirin resistance by any test was 51.7%. Aspirin resistance per individual test did not differ between women with and without recurrent HD. Aspirin resistance measured by any test occurred more frequently in women without recurrent HD (p < 0.01), irrespective of low-molecular-weight heparin. Conclusions: No relation could be demonstrated between recurrent HD and aspirin resistance per test, measured up to 16 years after pregnancy. On the contrary, complementary aspirin resistance measurements were encountered more frequently in women without recurrent HD.